Metagenomic next-generation sequencing assists in the diagnosis of visceral leishmaniasis in non-endemic areas of China - Zhao, Rui; He, Guilun; Xiang, Lin; Ji, Melinda; He, Rongheng; Wei, Xudong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionLeishmaniasis, a protozoan disease caused by infection by Leishmania, is a critical issue in Asia, South America, East Africa, and North Africa. With 12 million cases globally, leishmaniasis is one of the most serious neglected tropical diseases worldwide. Direct identification of infected tissues is currently the primary method of diagnosis; however, the low sensitivity and inconvenience of microscopic examination in detecting amastigotes, parasitic manifestations of Leishmania, leads to the possibility of misdiagnosis, delayed diagnosis, and underdiagnosis.MethodsWith the development of metagenomic nextgeneration sequencing (mNGS) technology for pathogen identification, it is possible to detect specific nucleic acid sequences characteristic of Leishmania parasites, which opens new avenues for the more accurate diagnosis of leishmaniasis. In this study, we report two cases of leishmaniasis from Henan Province, China, in which Leishmania parasites were identified using mNGS technology, massively expediting diagnosis and treatment.ResultsOur report demonstrates that the mNGS method is applicable to peripheral blood samples (PB), which are far more readily available in clinical settings, in addition to bone marrow aspirate samples (BM), which are traditionally used for diagnosis of visceral leishmaniasis.ConclusionOur report validates the efficacy of mNGS technology as a rapid and accurate method of diagnosis for leishmaniasis.